2019
DOI: 10.1016/j.ssmph.2019.100407
|View full text |Cite
|
Sign up to set email alerts
|

Internal migration and the health of Indigenous Mexicans: A longitudinal study

Abstract: Rationale Indigenous peoples have historically comprised a substantial part of migration streams around the world, yet our understanding of the effects of migration on indigenous health is limited. Objective To explore the migration-indigenous health relationship by assessing the impact of internal migration on the self-rated health trajectories of indigenous Mexicans. Data and method Using three waves of data (2002–2012) from the Mexican Fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Evidence of an immi grant health and mor tal ity advan tage has been found among immi grants to the United States from every region of the world (Riosmena et al 2017), and stud ies have found com pa ra ble advan tages for for eignborn pop u la tions in other des ti na tion con texts, includ ing Canada, Australia, and countries of Europe (Anson 2004;Boulogne et al 2012;Guendelman et al 1999;Kennedy et al 2006;Malmusi et al 2010). Similar advan tages in health and mor tal ity out comes have been documented for inter nal migrants mov ing within a coun try (Chen 2011;LeónPérez 2019;Lu 2008).…”
Section: Explanations For the Immigrant Mortality Advantagementioning
confidence: 86%
“…Evidence of an immi grant health and mor tal ity advan tage has been found among immi grants to the United States from every region of the world (Riosmena et al 2017), and stud ies have found com pa ra ble advan tages for for eignborn pop u la tions in other des ti na tion con texts, includ ing Canada, Australia, and countries of Europe (Anson 2004;Boulogne et al 2012;Guendelman et al 1999;Kennedy et al 2006;Malmusi et al 2010). Similar advan tages in health and mor tal ity out comes have been documented for inter nal migrants mov ing within a coun try (Chen 2011;LeónPérez 2019;Lu 2008).…”
Section: Explanations For the Immigrant Mortality Advantagementioning
confidence: 86%
“…Immigrant pop u la tions in the United States often have bet ter health out comes and lon ger life expec tan cies than their non im mi grant coun ter parts. An immi grant health and mor tal ity advan tage has been a recur rent find ing in demo graphic and pop u la tion health research and has been documented among migrants from all regions of the world (Riosmena et al 2017), in numer ous des ti na tion con texts (Anson 2004;Boulogne et al 2012;Guendelman et al 1999;Kennedy et al 2006;Malmusi et al 2010), and even among inter nal migrants within a coun try (Chen 2011;LeónPérez 2019;Lu 2008). This pat tern has been dubbed a "par a dox" in part because the mor tal ity pat terns of immi grant pop u la tions often do not cor re spond to their social posi tion in a coun try's ethnoracial hier ar chy (Bakhtiari 2021;Markides and Rote 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, indigenous migrants -especially children and adolescents -face significant challenges in terms of language barriers (Colmenares-Roa et al, 2017) and unfamiliar cultural practices in the urban zones where they arrive (León-Pérez, 2019), and are subject to marginalization (Franco-García, 2016). Furthermore, they experience inequalities in general health outcomes (Juárez-Ramírez et al, 2014) and, in the case of children below five years of age, in nutritional status (Ortega et al, 2012).…”
Section: Introductionmentioning
confidence: 99%